Hydrogelogical characterization of a waste rock pile and bedrock affected by acid mine drainage from geophysical survey - Moreira, Cesar Augusto [UNESP]; Casagrande, Matheus Felipe Stanfoca [UNESP]; Siqueira Buchi, Fernanda Miranda de [UNESP]; Targa, Debora Andrade [UNESP] (Springer, 2020)
Mining activities are known for the profound changes they cause in the environment, especially those related to environmental liabilities generated by these enterprises. One major concern of this sector relies on the acid mine drainage (AMD) process, which is formed by the exposure of sulfide minerals to oxidizing conditions. As a result, the production of low-pH saline waters favors the mobilization of heavy metals to the environment. In the last decades, the characterization and monitoring of contamination plumes have become more feasible due to the application of geophysical tools, more precisely the DC resistivity geophysical method. Thus, the aim of the present study is the application of electrical resistivity tomography to understand the hydrogeological dynamic of a waste rock pile in the Osamu Utsumi uranium mine, with the identification of preferred groundwater and AMD flow. The analysis of the 2D geophysical products allowed the differentiation of high salinity water accumulation zones (< 40 ohm m) in the interior of the pile. Likewise, the evaluation of the pseudo-3D model generated by the interpolation of 2D sections was crucial for the recognition of low resistivity zones within the bedrock, possibly controlled by fractures that work as recharge zones between the waste rock pile and the fractured aquifer. The identification of discharge and recharge zones related to the fractures system is a fundamental step for planning and actions to prevent water-sulfides interaction process, which is responsible for the generation of AMD, and also the installation of groundwater pumping systems.
Keywords: Mining; AMD; Aquifer; Recharge; Discharge; DC resistivity